2012
DOI: 10.2151/jmsj.2012-503
|View full text |Cite
|
Sign up to set email alerts
|

Radar Analysis on the Interaction between Southwesterly Monsoonal Flow and Circulation Associated with Typhoon Morakot (2009)

Abstract: This study investigates the mesoscale interaction of typhoon circulation and southwesterly flow during the passage of Typhoon Morakot (2009) over Taiwan using radar observations. Single Doppler radar analysis characterized typhoon features with remarkably distant rainbands, and identified the strong southwesterly monsoonal flow with a maximum speed of more than 45 m s -1 in the southern flank of distant rainbands. Dual-Doppler synthesized winds elucidated a confluent mechanism on the northern side of the rainb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Therefore, they can offer different areas of overlapping scan coverage, which are available for dual-Doppler radar wind synthesis. Wei et al (2012) have discussed that the long baseline between Chiku and Kenting radar would smooth the synthesized wind field due to coarse sampling. The relatively short baseline between the Makung and Chiku radar, however, can improve the horizontal resolution of synthesized wind to 1.5 km.…”
Section: Data Source and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, they can offer different areas of overlapping scan coverage, which are available for dual-Doppler radar wind synthesis. Wei et al (2012) have discussed that the long baseline between Chiku and Kenting radar would smooth the synthesized wind field due to coarse sampling. The relatively short baseline between the Makung and Chiku radar, however, can improve the horizontal resolution of synthesized wind to 1.5 km.…”
Section: Data Source and Methodologymentioning
confidence: 99%
“…Hsu et al (2010) learned that the SW flow in the Typhoon Morakot case supplied abundant moisture and formed a large-scale convective region, which was much larger than the size of the typhoon vortex. Wei et al (2012) demonstrated that Typhoon Morakot was embedded within a wide low pressure zone, which slowly moved westward under the extension of the subtropical ridge. The low pressure system introduced the intense SW flow from the Bay of Bengal reaching to the east of Taiwan carrying abundant moisture (Fig.…”
Section: Synoptic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Morakot was impacting Taiwan, the strong southwesterly flow converged with the northwesterly flow around the TC at low levels over the southern Taiwan Strait to form a primary rainband that was highly asymmetric with deep convection especially to the south of the TC center, as shown in Fig. 5 and many observational studies (e.g., Chen et al 2010;Jou et al 2010;Wei et al 2012). While this persistent, asymmetric rainfall pattern was also consistent with the northerly vertical wind shear (VWS) of about 5 m s 1 (Corbosiero and Molinari 2002;Chien and Kuo 2011;Wang et al 2012), the inner core of Morakot was weak and the rainbands were largely collocated with the outer circulation far from the center (Fig.…”
Section: Morakot Goni Etaumentioning
confidence: 73%
“…Wang et al (2015) studied the convective-scale processes and interaction between the updrafts of convective cells inside this rainband and the background VWS. This VWS was associated with a westerly low-level jet (LLJ) of about 45 m s 1 near 1 km in height (also Wei et al 2012), and thus had a hairpin shape in the hodograph. Below the LLJ, the interaction would produce negative (positive) dynamic pressure perturbations (pd') ahead and east (behind and west) of convective updrafts, as is typically found in midlatitudes (Rotunno and Klemp 1982;Klemp 1987).…”
Section: Morakot Goni Etaumentioning
confidence: 99%